2007
DOI: 10.1002/jcu.20331
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and pulsatility index increase in capsular branches of testicular artery: Indicator of impaired testicular microcirculation in varicocele?

Abstract: Increased RI and PI of capsular branches of testicular arteries on spectral Doppler examination may be an indicator of impaired testicular microcirculation in patients with clinical varicocele. Further studies addressing the correlations with sperm counts are needed to determine the cut-off values for these indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…Unsal et al found a significant difference in the RI and PI of the CA in varicocele patients compared to a control group [18]. Keeping in mind that there was a small number of cases in their study, the authors pointed out that these indices may be an indicator of impaired testicular microcirculation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Unsal et al found a significant difference in the RI and PI of the CA in varicocele patients compared to a control group [18]. Keeping in mind that there was a small number of cases in their study, the authors pointed out that these indices may be an indicator of impaired testicular microcirculation.…”
Section: Discussionmentioning
confidence: 88%
“…The effects of varicocelectomy on semen parameters and on pregnancy rates are well studied, but relatively little is known about the changes in the microvasculature of the testicles after surgery [5][6][7][8][9]. A few years ago, different research groups evaluated the microhemodynamics of the testes after varicocelectomy and reported different results [17,18]. The changes in the microhemodynamics of the testes recently became a hot topic yet again, with some authors trying to find a correlation between CDUS parameters and surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies [7,8] evaluating testicular microcirculation with color duplex ultrasonography, however, have shown no significant difference in testicular blood flow between patients with varicoceles and control groups. In a recent study using newer power Doppler ultrasonography, Unsal et al [9 ] has shown significant increase in resistance to blood flow as measured by the resistive index and pulsatility index of capsular branches in varicocele patients compared with controls. They concluded that resistive Purpose of review To review the role of varicocele repair in the treatment of male infertility.…”
Section: Testicular Blood Flowmentioning
confidence: 96%
“…As a noninvasive method color/spectral Doppler ultrasound analysis was tried to provide valuable information to assess the hemodynamic changes and testicular microcirculation status in cases of clinical varicocele. The significant increase in resistance index (RI) and pulsatility index (PI) values of capsular arteries may be an indicator of impaired testicular microcirculation, but the cutoff values for this index has not been determined [2]. In this technique, relatively advanced stages of scrotal scarring can be detected when there is profound and substantial morphological deterioration in the scrotal parenchyma and decreased volume.…”
Section: Introductionmentioning
confidence: 99%